Therapeutic advances in type 1 myotonic dystrophy complicated with type 2 diabetes mellitus - Luo, Lin; Zhu, Changsen; Yang, Shaona; Sun, Yuan; Rong, Muyang; Li, Tianrong (Frontiers in Neurology, 2025)
Myotonic Dystrophy (DM) is a hereditary muscle disorder characterized by progressive muscle weakness, myotonia, and multi-system dysfunction. Based on clinical and genetic features, DM can be classified into Type 1 (Type 1 Myotonic Dystrophy, DM1) and Type 2 (Type 2 Myotonic Dystrophy, DM2), with DM1 being the most common subtype in adulthood. Diabetes, a metabolic disease, is defined by persistent hyperglycemia, typically resulting from insufficient insulin secretion or impaired insulin action. Among the various forms of diabetes, Type 2 Diabetes (T2DM) has the highest prevalence, accounting for approximately 90% of all cases. Research has shown that individuals with Myotonic Dystrophy Type 1 (DM1) often experience comorbid Type 2 Diabetes (T2DM), a phenomenon that not only significantly increases the clinical burden but is also closely associated with poor prognosis, severely impacting patients’ quality of life. This review provides a comprehensive analysis of the latest research on insulin resistance in DM1 patients, shedding light on the underlying mechanisms of DM1-related T2DM. Additionally, it explores the common comorbidities shared by DM1 and T2DM, including those affecting the muscular, respiratory, cardiovascular, endocrine, and nervous systems, as well as cancer and depression. Finally, this article summarizes the most recent therapeutic strategies for managing DM1 with T2DM, focusing on glucose-lowering medications combined with emerging targeted therapies that address the core pathophysiology of DM1, showing promising preclinical outcomes. This review aims to provide a theoretical foundation for future research and clinical practice in the management of DM1 complicated by T2DM.